Platelet Cofactors as Plasma Components of the Intrinsic Blood Clotting Mechanisms - Mammen, Eberhard F.; Yoshinari, Motoyuki; Seegers, Walter H. (Thrombosis and Haemostasis, 1961)
The method for the assay for platelet cofactors has been overhauled to make allowance for an adequate and uniform supply of Ac-globulin. Thrombin is added at zero time to reduce variability of response in the activation of prothrombin. The potency of purified platelet cofactor I is about twice that of platelet cofactor II (autoprothrombin II). The total mass of platelet factor 3 plus platelet cofactor I or platelet cofactor II is much greater in the conversion of a given amount of purified prothrombin to thrombin than when brain thromboplastin is used.In plasma and serum from the human being barium carbonate adsorbs platelet cofactor II, and ether extraction frees activity that is not adsorbed on barium carbonate before ether extraction. The extract contains an inhibitor(s) of prothrombin activation. The inhibition is strong in the intrinsic as well as the extrinsic prothrombin activation mechanisms. In the case of bovine plasma barium carbonate adsorption leaves the plasma richer in platelet cofactor activity and in that respect it differs from the plasma from human beings. Dog plasma and serum is comparable to that from man than the bovine species.The lipids extracted from plasma or serum with ether are predominantly anticoagulant. Since platelet cofactor I activity disappears during the clotting of blood, we think that a function of platelet cofactor I is to be the receptor for an anticoagulant. Then as autoprothrombin II arises from prothrombin it serves as a procoagulant and is not retarded by the anticoagulant neutralized by platelet cofactor I.